Untapped Reserves: Controlling Primordial Follicle Growth Activation. Issue 3 (March 2018) - Kallen, Amanda; Polotsky, Alex J.; Johnson, Joshua
Abstract : Even with the benefit of assisted reproductive technologies (ART), many women are unable to conceive and deliver healthy offspring. One common cause of infertility is the inability to produce eggs capable of contributing to live birth. This can occur despite standard-of-care treatment to maximize the recovery of eggs from growing ovarian follicles. Dormant primordial follicles in the human ovary are a 'reserve ' that can be exploited clinically to overcome this problem. We discuss how controlling primordial follicle growth activation (PFGA) can produce increased numbers of high-quality eggs available for fertility treatment(s). We consider the state of the art in interventions used to control PFGA, and consider genetic and epigenetic strategies on the horizon that might improve compromised oocyte quality to increase live births. Highlights: Women who are currently considered to be infertile due to poor egg quality or are at risk of ovarian failure may have new options. Ovarian cortex can be isolated, cryopreserved, and redelivered to the ovary, whereupon ovarian function might resume. Ovarian cortex tissue is also currently being used in attempts to produce mature fertilizable eggs in vitro . Mechanisms that control PFGA have been identified and used to induce follicle growth in mouse models (genetic and in vitro follicle cultures), as well as in experimental human clinical interventions. In vitro follicle culture offers control over follicle development (and access to the follicles themselves from early developmental stages) such that modern genetic/epigenetic tools might be used to improve egg quality. For example, genome-editing reagents (e.g., CRISPR/Cas9) might be injected into growing follicles to correct defects compromising egg quality. This type of technology also aims to correct disease states in offspring; however, these newer approaches in reproductive medicine, although promising, are still in their infancy.